Pokémon : Scyther Vs Charizard [anglicky]. Book 4 - West, Tracey, 1965- (Orchard Books, 2021)
Scyther and Charizard are two of the most powerful Pokémon Ash has ever encountered. But this makes them hot-headed and very difficult to control. When the two Pokémon face each other in battle, it's chaos! Can Ash discover the secret to connecting to wayward Charizard, and pull off the most epic battle so far?